Schwann Cell Expressed Nogo-B Modulates Axonal Branching of Adult Sensory Neurons Through the Nogo-B Receptor NgBR - Eckharter, Christoph; Junker, Nina; Winter, Lilli; Fischer, Irmgard; Fogli, Barbara; Kistner, Steffen; Pfaller, Kristian; Zheng, Binhai; Wiche, Gerhard; Klimaschewski, Lars; Schweigreiter, Rüdiger (Frontiers in Cellular Neuroscience, 2015)
In contrast to the central nervous system (CNS) nerve fibers do regenerate in the peripheral nervous system (PNS) although in a clinically unsatisfying manner. A major problem is excessive sprouting of regenerating axons which results in aberrant reinnervation of target tissue and impaired functional recovery. In the CNS, the reticulon protein Nogo-A has been identified as a prominent oligodendrocyte expressed inhibitor of long-distance growth of regenerating axons. We show here that the related isoform Nogo-B is abundantly expressed in Schwann cells in the PNS. Other than Nogo-A in oligodendrocytes, Nogo-B does not localize to the myelin sheath but is detected in the ER and the plasma membrane of Schwann cells. Adult sensory neurons that are cultured on nogo-a/b deficient Schwann cells form significantly fewer axonal branches versus those on wildtype Schwann cells, while their maximal axonal extension is unaffected. We demonstrate that this effect of Nogo-B on neuronal morphology is restricted to undifferentiated Schwann cells and is mediated by direct physical contact between these two cell types. Moreover, we show that blocking the Nogo-B specific receptor NgBR, which we find expressed on sensory neurons and to interact with Schwann cell expressed Nogo-B, produces the same branching phenotype as observed after deletion of Nogo-B. These data provide evidence for a novel function of the nogo gene that is implemented by the Nogo-B isoform. The remarkably specific effects of Nogo-B/ NgBR on axonal branching, while leaving axonal extension unaffected, are of potential clinical relevance in the context of excessive axonal sprouting after peripheral nerve injury.